Cognitive Strategies and Their Linguistic Foundations in Translation Between French and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides a scientific and theoretical analysis of the cognitive strategies used in the translation process between French and Uzbek, as well as their linguistic foundations. Translation activity requires not only finding equivalence between language units, but also a deep study of the processes of perception, conceptualization, association and thinking that occur in the translator's mind. In particular, the analytical structure of the French language and the agglutinative nature of the Uzbek language impose additional cognitive tasks on the translator. The article highlights strategies such as mental modeling, context restructuring, logical categorization, and equivalence optimization used in processing grammatical, lexical, pragmatic and cultural differences between these two languages. It also considers effective methods for perceiving metaphors and conceptual structures, correctly interpreting cultural connotations, and preserving the communicative purpose of the text during the translation process. This study identifies the role of the cognitive approach in improving the quality of translation and provides scientifically based conclusions on the further improvement of French-Uzbek translations.